Isolation and Characterization of Phenolic Compounds and Anthocyanins from Murta (Ugni Molinae Turcz.) Fruits. Assessment of Antioxidant and Antibacterial Activity - Zuniga-Navarro, G; Yanez-Catalan, L; Contreras-Arredondo, R; Junqueira-Conceicao Goncalve, M (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
Berry fruit consumption has become important in the promotion of human health, mainly due to their phenolic compounds, which have been associated with protection against different pathologies, as well as antimicrobial and other biological activities. Consequently, there has been a growing interest in identifying natural antioxidants and antimicrobials from these plants. This study aimed to characterize the phenolic chemical composition and anthocyanin profile of murta (Ugni molinae Turcz.) fruit, and to evaluate the antioxidant and antimicrobial activity of its extracts (ethanolic and methanolic). LC/MS of the ethanolic extracts showed the presence of three major compounds: caffeic acid 3-glu, quercetin-3-glu and quercetin, while in the methanolic acid extract they were cyanidin-3-glucoside, pelargonidin-3-arabinose and delphinidin-3-glucoside. The antioxidant activity of ethanolic extracts (DPPH• and ORAC assays) was higher than that of methanol acid extracts or purified anthocynins. Furthermore, the methanol acid extract showed an inhibitory activity against the bacteria E. coli and S. typhi similar to that of standard antibiotics. The results suggest that the antioxidant activity of the ethanolic extract is regulated by the high content of phenolic compounds and the fruit s characteristic color is due to the content of pelargonidin-3-arabinose and delphinidin-3-glucoside. The obtained results demonstrated the appreciable antioxidant and antibacterial activities, providing opportunities to explore murta extracts as biopreservatives. © 2015 by the authors; licensee MDPI.